Genetic Factors and Environmental Influences during Innovation Explosion on Personality Development. A Review - Giannoukou, Ioanna (Technium Social Sciences Journal, 2024)
The development of personality is an ongoing and lifelong process that commences at conception and endures throughout an individual’s lifespan. Both genetic factors and environmental variables contribute to its influence. Genetic variables constitute the fundamental underpinnings of personality development, while the environment furthermore assumes a significant role. Environmental influences, such as parents, family, friends, employment, and various social groups, significantly influence an individual’s developmental trajectory. Therefore, personality development is a multifaceted process influenced by the interplay of hereditary and environmental influences, with both playing a role in facilitating the construction of one’s personality. The primary objective of this systematic review is to investigate the influence of genetic and environmental factors on the development of personality, encompassing both infancy and adulthood. This study addresses the abovementioned issue by analyzing the most up-to-date research findings from the past decade. This study’s experimental procedures and techniques are described in the following section. This study presents a comprehensive overview of the existing literature investigating the impact of genetic and environmental factors on personality development. Fifteen scholarly research publications were chosen, focusing on individuals mostly in their youth and exploring the impact of genetic and environmental factors. The primary objective of this study is to address inquiries about the genetic impact, environmental role, and the combined contribution and interaction of these elements, as well as to elucidate the underlying causes of this connection and influence. The inclusion criteria for the papers encompassed several factors: language, relevance to the subject matter, age range of participants, publication time, journal of publication, study type, and methodological quality. In conclusion, while genetic factors and the environment play critical roles in shaping individuals, their complex interplay truly defines outcomes. Neither genes nor environment dictate destinies in isolation; their combined, intricate dance sculpts the vast diversity of human experiences. This interplay is fundamental to psychology, medicine, sociology, and even policymaking.